Dialogic processes that enable student teachers' learning about pupil learning in mentoring conversations in a Lesson Study field practice. (February 2018) - Bjuland, Raymond; Helgevold, Nina
Abstract: This study investigates dialogic processes in student teachers' mentoring conversations in field practice, where Lesson Study (LS) was used as a context for establishing a dialogic learning community in one student group in science. We apply an analytical framework associated with Sociocultural Discourse Analysis to identify utterances that have the potential to create a dialogic space and contribute to 'interthinking' among the participants. The findings show the important role of the mentor teacher as a facilitator and a 'knowledgeable other', challenging the student teachers to reflect on chosen activities using predictions and detailed observations related to pupils' learning. Highlights: We examine dialogic processes in student teachers' mentoring conversations. LS is used as a context to establish dialogic spaces of 'interthinking'. The mentor teacher's role as the 'knowledgeable other'.